Global Trend of Numeracy Research: A Bibliometric Analysis Using Scopus Database - Saputri, Veni; Kusumah, Yaya Sukjaya; Turmudi, T; Jupri, Al (Universitas Negeri Gorontalo, 2025)
The study of numeracy has grown rapidly in the last decade, especially after the implementation of the Minimum Competency Assessment (MCA) in Indonesia since 2021. This research aims to map the development of numeracy research globally through bibliometric analysis, with a computational mapping approach using Bibliometrix in RStudio and VOSviewer. Article data was taken from the Scopus database published from 2014 to 2023. Article titles, keywords and abstracts guided the search process with reference to the keyword ‘numeracy’. A total of 811 documents were identified, of which 699 were cited. The analysis showed an increasing publication trend, with a predominance of contributions from specific countries and institutions, and a thematic focus on academic achievement, cognitive ability and early literacy. Keyword visualisations also reveal interrelationships between topics and show that the integration of technology in numeracy learning is still relatively limited. The findings provide a comprehensive overview of the structure and direction of numeracy research and open up opportunities for further exploration in digital and interdisciplinary learning contexts.